2021
DOI: 10.7759/cureus.13124
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin-Aldosterone System Inhibitors and COVID-19: A Meta-Analysis and Systematic Review

Abstract: Introduction Increased virulence, the severity of illness, and mortality have all been hypothesized with respect to angiotensin-converting enzyme inhibitor (ACEi)/angiotensin receptor blocker (ARB) use in coronavirus disease 2019 (COVID-19) infection. Our study aims to assess whether ACEi/ARB use in patients with COVID-19 conferred worsened severity of illness or increased mortality. Additionally, we explore the possibility of an unearthed protective benefit due to their interruption of the RAS signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This study was not the first systematic review and meta‐analysis to assess the associations between RAAS inhibitor use and COVID‐19 outcomes. As of December 2021, at least 52 meta‐analyses had been conducted, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 each of which pooled studies that have a critical risk of bias. Critical biases limit confidence in the evidence produced by these meta‐analyses as much as they do in each of the studies that t...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was not the first systematic review and meta‐analysis to assess the associations between RAAS inhibitor use and COVID‐19 outcomes. As of December 2021, at least 52 meta‐analyses had been conducted, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 each of which pooled studies that have a critical risk of bias. Critical biases limit confidence in the evidence produced by these meta‐analyses as much as they do in each of the studies that t...…”
Section: Discussionmentioning
confidence: 99%
“… 6 At least 52 meta‐analyses have assessed associations between RAAS inhibitor use and COVID‐19 risk by collating parts of that body of research. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 However, little attention has been paid to selection bias, or other biases for that matter, which may distort the interaction between RAAS inhibitor use and COVID‐19.…”
mentioning
confidence: 99%
“…Moreover, the increase in the severity of illness in patients with CAD seen in our study may also be attributed to the prevalent use of ARBs and ACEI drugs among such patients due to the potential upregulation of ACE-2 receptors [23]. Nevertheless, a recent systematic review and meta-analyses revealed no significant difference in the illness severity of COVID-19 infection between ARB/ACEI users and nonusers [24]. Thus, future focus should be implemented on other comorbidities associated with CAD and their role in the mortality and severity of the infection while adjusting for other confounding variables.…”
Section: Discussionmentioning
confidence: 46%
“…It has been hypothesized that increases in ACE2 expression, resulting from the use of these medications, can increase the virulence of SARS-CoV-2. Several case studies have found that RAAS inhibitors are associated with decreased severity of COVID-19, lessened organ injury, and reduced inflammation [48,49]. Evidence also shows that RAAS inhibitors, including ARBs and ACE inhibitors, protect against Ang ll/Ang 1-7 imbalance [50,51].…”
Section: Discussionmentioning
confidence: 99%